Exploring challenges in COIL: an analysis of students' buy-in - Monica Skaten; Thor Erik Sortland (European Teacher Education Network, 2024)
Collaborative Online International Learning (COIL)-projects has many challenges. Contrary to most papers on Virtual Exchange (VE) in general, or the COIL-method specifically, we analyse some of these challenges. We have found it productive to analyse the lack of students' engagement and activity through the concept of buy-in. Buy-in, within the educational sphere, refers to the degree in which individuals accept and commit to a specific educational approach. The main discourse of COIL focuses on its wide potential for skills-acquisition among participating students. What is less researched and analysed is the dynamics of challenges that are observed in these programmes, how they occur, develop and manifest in the student body. Challenges are often listed or mentioned briefly, without adequate attention provided as to why they happen or how this impacts the students experience over time (with some exceptions see; O'Dowd and Ritter, 2006). This paper aims to provide such an analysis and engage other scholars in a research-based discussion on the challenges associated with COIL to gain a fruitful understanding and develop inclusive and impactful COIL-modules.